Reparasi Gigi Tiruan Lepasan pada Pasien Stroke dengan Keterbatasan Mobilitas melalui Home Care: Laporan Kasus - IGAM Oka Lestari; Fitria Rahmitasari; Paulus Budi Teguh (Jurnal Kesehatan Amanah, 2026)
Stroke patients often experience mobility limitations, which impacts access to dental health services, including denture care. This condition can lead to unmanaged dentures, thus impairing masticatory function, nutritional status, and quality of life. A home care approach is one solution to improve access to dental services for patients with special needs. To report the management of direct removable denture repair in a single visit in a stroke patient using a home care approach and to evaluate the clinical outcomes. This study is a case report of a 77-year-old male patient with a history of recurrent stroke and limited mobility. Examination and treatment were performed at the patient's home. The direct removable denture repair was performed using autopolymerizing acrylic resin in a single visit. Following repair, the denture demonstrated improved retention and stability and was reusable. The patient reported improved comfort while eating without any pain or post-procedure complications. One-visit denture repair through a home care approach is an effective and efficient method for stroke patients with limited mobility and has the potential to improve their quality of life through rapid restoration of oral function.